2013
DOI: 10.1016/j.ajpath.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Genetic Susceptibility to Breast Cancer

Abstract: Genome-wide association studies have identified 72 loci associated with breast cancer susceptibility. Seventeen of these are known to predispose to other cancers. High-penetrance susceptibility loci for breast cancer usually result from coding alterations, principally in genes involved in DNA repair, whereas almost all of the associations identified through genome-wide association studies are found in noncoding regions of the genome and are likely to involve regulation of genes in multiple pathways. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 102 publications
2
35
0
2
Order By: Relevance
“…Combining the results with a previously published summary of human BrCa risk loci (Ghoussaini et al 2013) revealed that 5 of the 20 Mdq were syntenic with previously detected BrCa risk loci (Figure 7, Table 4). The potential significance of these loci as well as the remaining QTL will be addressed further below.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Combining the results with a previously published summary of human BrCa risk loci (Ghoussaini et al 2013) revealed that 5 of the 20 Mdq were syntenic with previously detected BrCa risk loci (Figure 7, Table 4). The potential significance of these loci as well as the remaining QTL will be addressed further below.…”
Section: Resultssupporting
confidence: 70%
“…Most recently, the use of genome-wide association studies (GWAS) in human populations has identified 72 loci associated with a modest (relative risk <1.5) increase in BrCa risk (Ghoussaini et al 2013). The identification of these loci represent an enormous opportunity to further our understanding of BrCa, but this work also points to the complexity of the disease, since all of these common alleles have only modest effects and likely interact in complex ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El metaanálisis realizado por Ghoussaini y colaboradores muestra evidencias de que la presencia de un familiar en primer grado con CGM incrementa el riesgo relativo en 2,1 y que este incremento es inversamente proporcional a la edad de inicio en el familiar afectado (Ghoussaini et al, 2013). En general, se considera que el riesgo de herencia es mayor según el número de familiares afectados y la cercanía del parentesco.…”
Section: Discussionunclassified
“…Many of the identified risk factors are non-modifiable, however, and thus far, only a small percentage of breast cancer risk has been successfully linked to genetic inheritance (Oldenburg et al, 2007; Ghoussaini et al, 2013). Considerable research has investigated the associations between daytime behaviors, such as alcohol consumption (Smith-Warner et al, 1998), smoking (Xue et al, 2011), diet (Boyd, 2003), and physical activity (Vainio et al, 2002), and individual risk for breast cancer.…”
Section: Introductionmentioning
confidence: 99%